7(x-3)=-3x+89

Simple and best practice solution for 7(x-3)=-3x+89 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-3)=-3x+89 equation:


Simplifying
7(x + -3) = -3x + 89

Reorder the terms:
7(-3 + x) = -3x + 89
(-3 * 7 + x * 7) = -3x + 89
(-21 + 7x) = -3x + 89

Reorder the terms:
-21 + 7x = 89 + -3x

Solving
-21 + 7x = 89 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-21 + 7x + 3x = 89 + -3x + 3x

Combine like terms: 7x + 3x = 10x
-21 + 10x = 89 + -3x + 3x

Combine like terms: -3x + 3x = 0
-21 + 10x = 89 + 0
-21 + 10x = 89

Add '21' to each side of the equation.
-21 + 21 + 10x = 89 + 21

Combine like terms: -21 + 21 = 0
0 + 10x = 89 + 21
10x = 89 + 21

Combine like terms: 89 + 21 = 110
10x = 110

Divide each side by '10'.
x = 11

Simplifying
x = 11

See similar equations:

| -7+3x-2x=17 | | 5y^5=20 | | 3500+1680x=175000+550x | | 8(3n-8)=8 | | 5.9-p=2 | | x-153=55+9x | | 6.3=7.0x | | -4.5(7x-6.5)=-23.5 | | 52-4x=10-10x | | 3x-2(x-3)+4(x+1)=-5 | | 2x-102-10x=42 | | -9(5-5.5k)=26.5 | | 14-8m= | | -77-10x=165+x | | 5ab*3= | | 5r-14=-44 | | 10x-1=6x+10 | | =9xy^2+6xy-5x | | 24+8y-16w= | | 2(7x-13)=16 | | 5x+(x+2)-3(x-4)=35 | | 5x+3+3x=83 | | 2(7x+13)=16 | | 2x-5+12=7(x-2) | | 3x-7=5+6x | | -2d-9.5d=-2.15 | | 8x+28=60 | | -3(-3r-6)=63 | | 8.5x=6y-c | | 6x-12=20x | | x-4(x+1)-2(x+3)=-60 | | 2(3x-6)=20x |

Equations solver categories